Murine natural killer cell interactions with a fungal target, Cryptococcus neoformans. - Hidore, M R (1989)
Earlier investigations have shown that murine natural killer (NK) cells bind to and inhibit the growth of the fungal pathogen Cryptococcus neoformans in vitro and in vivo. To define the stages of NK cell-mediated inhibition of C. neoformans growth and the requirements for the completion of these stages, the events which lead to cryptococcal growth inhibition were compared with those previously elucidated for NK cell-mediated tumor cell lysis. Our data indicate that NK cell-cryptococci binding is a distinct event that precedes inhibition; is temperature independent, although it is slowed at 4 degrees C; and is Mg2+ dependent. In contrast to binding, NK cell-mediated cryptococcal growth inhibition is temperature, Mg2+, and Ca2+ dependent. The removal of Ca2+ by EDTA addition within 3 h after maximal NK cell-cryptococci binding significantly reduced cryptococcal growth inhibition, indicating that Ca2+ is required either late in the NK cell trigger stage or early in the inhibitory stage. These stages and requirements are similar to those previously demonstrated for the model of NK cell-mediated tumor cell lysis; however, the NK cell-cryptococci interactions are somewhat slower than the interactions which culminate in the lysis of the YAC-1 tumor cell targets. These results suggest that C. neoformans cells, although structurally distinct from the standard tumor cell targets, are capable of similar cell-to-cell interactions with NK effector cells as the tumor cell targets.